2022
DOI: 10.3390/app12136736
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Test of Sleeve Grouted Lapping Connectors under Uniaxial Tension and High-Stress Repeated Tension and Compression Loading

Abstract: In this study, uniaxial tension tests and high-stress repeated tension and compression tests were conducted on 32 APC (all vertical members precast in concrete structures) connectors. After high-stress repeated tension and compression, the bearing capacities of the connector specimens improved due to the strengthening of the steel bars, and the ductility of the specimens was reduced due to the further development of cracks between the steel bars and the grout. The residual deformation values of the specimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Zhi et al [15] discuss the seismic performance of nine full-scale shear walls, including seven precast specimens and two cast-in-place specimens, and proved that shear walls with metal bellows at the joint have good structural properties. Yu et al [16] performed incremental tensile load tests on 16 grouted sleeve lap connectors and 3 grouted splice connectors, and it was found that the tensile capacities of the grouted sleeve lapping connectors were up to 2.45 times that of the grouted splice connectors when the sleeve inner surfaces were smooth. All of the grouted sleeve lapping connectors failed via a bar tensile fracture or bar-grout.…”
Section: Introductionmentioning
confidence: 99%
“…Zhi et al [15] discuss the seismic performance of nine full-scale shear walls, including seven precast specimens and two cast-in-place specimens, and proved that shear walls with metal bellows at the joint have good structural properties. Yu et al [16] performed incremental tensile load tests on 16 grouted sleeve lap connectors and 3 grouted splice connectors, and it was found that the tensile capacities of the grouted sleeve lapping connectors were up to 2.45 times that of the grouted splice connectors when the sleeve inner surfaces were smooth. All of the grouted sleeve lapping connectors failed via a bar tensile fracture or bar-grout.…”
Section: Introductionmentioning
confidence: 99%